Design and Build Information System of the Joper Chicken Plasma Core at PT. Barokah - Chanif Sari; Hedi Pandowo (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2020)
Breeding joper chickens with a partnership system is a form of business that is currently on the rise, breeding in partnership is a form of cooperation between breeders (plasma) and companies (nucleus). The yields will be divided according to the percentage agreed upon in the contract agreement that has been made between plasma and nucleus. It takes approximately 12 weeks for the farmer to raise the chickens until harvest. During this period, breeders must take care of the chickens maximally so that it is hoped that the harvest will be profitable for both the farmer as the plasma and the company as the nucleus. There needs to be extra careful management in the process of cultivating joper chickens because chicken farming can be said to have a high enough risk. Therefore, this system was built in order to overcome problems such as irregular feeding or vaccines, manual recording of daily chicken development, disease management and lack of insight into diseases that chickens often get, as well as weighing calculations that are still being carried out. Manually. So that by overcoming these problems the crop yields will increase and the level of productivity of chickens is controlled. The tools used in making this system are Visual Basic. Application design method using ProtoTyping method.